2021
DOI: 10.36740/wlek202102102
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Analyze the Specificity of Chlamydial Heat Shock Protein (Chsp60) Antibodies to Diagnose Tubal Infertility

Abstract: The aim: To investigate the utility of testing for chlamydial heat shock protein 60 (CHSP60) antibodies in the diagnosis of tubal infertility. Materials and methods: All the collected samples were assayed for IgM and IgG antibodies to chlamydia trachomatis and chlamydial heat shock protein 60 (CHSP60) by using immunofluorescence and enzyme-linked immunosorbent assay (ELISA) techniques, respectively. Results: There were no substantial differences between antibodies to C. trachomatis in females with tubal infert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Paavonen and colleagues have shown that the presence of antibodies to heat shock protein-60 of C. trachomatis is associated with a higher risk of cervical cancer, also suggesting that the persistent infection by C. trachomatis is related to cervical tumors [ 103 ]. Others suggest that this protein is also involved in infertility, as previously stated by us [ 104 ].…”
Section: Chlamydia and Tumorigenesis Associationsupporting
confidence: 53%
“…Paavonen and colleagues have shown that the presence of antibodies to heat shock protein-60 of C. trachomatis is associated with a higher risk of cervical cancer, also suggesting that the persistent infection by C. trachomatis is related to cervical tumors [ 103 ]. Others suggest that this protein is also involved in infertility, as previously stated by us [ 104 ].…”
Section: Chlamydia and Tumorigenesis Associationsupporting
confidence: 53%